2016
DOI: 10.1007/s00415-016-8035-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and symptoms of intracranial arachnoid cysts: a population-based study

Abstract: To investigate the prevalence of intracranial arachnoid cysts in a large population-based sample. We also aimed to assess the association between arachnoid cysts and cognitive impairment, depression, epilepsy, headache, dizziness, previous head trauma, hip fractures, and mortality. A population-based cohort and nested case-control study. The sample comprised representative populations (n = 1235) aged ≥ 70 years. All participants underwent baseline neuropsychiatric examinations, including computed tomography (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 29 publications
1
38
4
1
Order By: Relevance
“…These results confirm previous conclusions (from other ethnic groups and locations) that these lesions are essentially benign, at least with regard to the investigated outcome. As previously mentioned, there is only one population‐based study that attempted to assess the association between arachnoid cysts and epilepsy in Sweden . In that study, none of 29 individuals with arachnoid cysts and 5 of 290 without arachnoid cysts had epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results confirm previous conclusions (from other ethnic groups and locations) that these lesions are essentially benign, at least with regard to the investigated outcome. As previously mentioned, there is only one population‐based study that attempted to assess the association between arachnoid cysts and epilepsy in Sweden . In that study, none of 29 individuals with arachnoid cysts and 5 of 290 without arachnoid cysts had epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…These lesions may be related to developmental abnormalities of the brain (primary cysts) or result from head trauma, previous infections, tumors, or surgery (secondary cysts) . Arachnoid cysts are often seen as incidental lesions not associated with any particular clinical manifestation . However, arachnoid cysts have also been associated with headache, vomiting, dizziness, and—more importantly—with seizures or epilepsy …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors showed that the individuals included in their study with or without arachnoid cysts had the same frequency of headache , dizziness, cerebral traumatic events, cognitive impairment and cognitive and depressive symptoms [14] Arachnoid cysts of the posterior temporal fossa are associated with partial temporal lobe agenesis and now there are argues if the temporal lobe agenesis is responsible for the cyst formation or if the agenesis is the consequence of the cyst formation [9] There are rare situation with de novo cyst formation [7] 6. Dismantling the arguments against Arachnoid cysts are representing just 1% from space occupying formations and a part of them ¼-1/3 are located in the posterior cerebral fossa, and is the second location after the middle cranial fossa [3] The most frequent location in children is the sylvian fissure and the middle cerebral fossa.…”
Section: Arguments To Argue the Thesismentioning
confidence: 99%